Penelitian Kasus Trachoma pada Murid Sekolah Dasar - Mu'tasimbillah Ghozi Mu'tasimbillah Ghozi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
Trachoma is a specific communicable keratoconjunctivitis, usually of chronic evolution caused by an agent belonging to the psittacosis - lymphogranuloma - trachoma group of atypical viruses and characterized by follicles, papillary hyperplasia, pannus, and in its later stages, by cicatrizadon